Addressing Language and Study Skills Challenges in Online Undergraduate EMI Courses - Lucas Kohnke; Andrew Jarvis (Education Sciences, 2023)
English-medium instruction (EMI) is taking hold within higher education in non-Anglophone settings, but there is insufficient research into the challenges students encounter when taking EMI courses online. This exploratory quantitative study conducted in Hong Kong examines the language and studying challenges faced by undergraduate students when in-person classes were suspended due to COVID-19. One hundred thirteen first- and second-year students completed a questionnaire, rating their perceived challenges in the areas of writing, speaking, reading, listening, and study skills. The results showed that they faced particular challenges with reading and study skills (especially self-motivation), as well as vocabulary range, which affected more than one skill. Corroborating existing research, students with less secondary school EMI experience reported greater challenges. As providing English for Academic Purposes (EAP) courses is a primary way to support the language skills of students in EMI settings, we offer guidance to EAP practitioners who seek to help their students overcome the challenges identified in this article. As online technology continues to deliver content in tertiary education, EAP courses must be closely aligned with the language and study skills needs of students in digital EMI environments.